EFFECTS OF SILVER AND LEAD NITRATES ON IMPLANTATION INTERFERENCE, MISCARRIGE AND TERATOGENICITY: A PRELIMINARY REPORT - ATANU KONER*, USHASI BHAUMIK, ARGHYA BANERJEE; SUDHANGSU K. GHOSAL (The Bioscan, 2015)
The present work elucidates the menacing effects of silver and lead nitrates on both the pregnant mice and developing embryos. Consequent upon the subcutaneous injection of different concentrations of AgNO3 and PbNO3 , the inseminated females were invariably confronted with episodes like preterm delivery, gastrointestinal complications, fetotoxicity and precocious parturition of congenitally malformed embryos.These stillborns, unlike the control embryos of the same age group, were destitude of eyes, ears and hair follicles. They ultra structurally displayed the presence of aberrant hepatocytes and renal corpuscles. The oral administration of these compounds to mated females generated a panoplyof augmented phenomena including implantation failure and disanchorage of placenta. Several mated mice developed intestinal neoplasia, lung tumor and other visceral anomalies.